A atuação histórica do exército na política nacional e a obra "Geopolítica do Brasil", do General Golbery do Couto e Silva: importância histórica e objetivos de um projeto político de poder - Seixas, Ivan Akselrud de (2019)
This dissertation aims to contribute to understand the nature of the participation of the national army in Brazilian politics, from the proclamation of the Republic to the creation of the Superior School of War (ESG) in 1948. In order to achieve this goal, a period under analysis for which a bibliographical revision of the political participation of the national army in the classic works "Soldados da Pátria" (2007) by the Brazilianist Frank D. McCann was chosen; "The Military Power" (1984), by the Brazilian historian Hélio Silva; "1964 - The conquest of the State - Political action, power and class coup", by Rene Armand Dreifus; "Anarchists and Communists," by John W. F. Dulles (1973); Military History of Brazil "by Nelson Werneck Sodré (2010). Considering that geopolitics gained importance for the military from the beginning of the twentieth century, a bibliographical revision on this topic was necessary, for which the books "Geopolitics of Brazil - the Silver Basin" (1997) and "Who has fear of geopolitics "(2015), both by social scientist Leonel Itaussu de Almeida Melo. The book "Geopolitics of Brazil" by General Golbery do Couto e Silva, an important Brazilian military intellectual in the area of geopolitics, was analyzed. This book was published in 1967, when General Golbery was the Chief of the National Information Service (SNI), an agency of the federal government for the control and repression of opponents of the military dictatorship, established in 1964, is the combination of several written texts for the courses taught by him at ESG, an institution that was one of the creators and a teacher. It was concluded that the national army had a strong presence in the main national political events, guaranteeing and maintaining the control of the governments of the national oligarchies, both in times of rupture and in the imposition of anti-popular policies by force. It is also concluded that the analyzed book authored by General Golbery of Couto e Silva is the expression and systematization of this military participation in politics, which differs from the nature of the participation of the military in the periods prior to the republican period, the integrity of national borders and war issues arising from border issues.